Hybrid transdermal drug delivery patch made from poly(p‐phenylene vinylene)/natural rubber latex and controlled by an electric field. Issue 6 (16th April 2018) - Niamlang, Sumonman; Paradee, Nophawan; Sirivat, Anuvat
Abstract: A flexible, natural rubber (NR) patch was developed for electrically controllable transdermal drug delivery. NR latex was crosslinked at various crosslinking ratios under the UV curing method. Ibuprofen (Ibu) was the model drug and was used as the dopant for poly( p ‐phenylene vinylene) (PPV) acting as the drug encapsulating host. For the pristine Ibu‐loaded NR patch, the amount of Ibu permeation increased with decreasing crosslink density and increasing electrical potential. For the Ibu‐doped PPV/NR patch, the amount of Ibu release−permeation also increased with increasing electrical potential and was higher than that of the pristine NR matrices. Without an applied electric field, the drug remained attached to the PPV during an initial period of 6 h. Under an applied electric field, the oxidation state of the conductive polymer was altered, the iontophoretic effect, pore formation in the NR matrix, expansion of the pore size in hair follicles and PPV chain expansion combined to increase the Ibu release−permeation amount. Thus, the flexible PPV/NR transdermal drug delivery patch was demonstrated to be effective in drug release−permeation based on the strength of the electrical potential, the crosslinking density and the presence of PPV as the encapsulation host. © 2018 Society of Chemical Industry Abstract : The flexible PPV/NR TDD patch has been demonstrated to enhance drug release−permeation based on the strength of the electrical potential, the crosslinking density and the presence of PPV as the encapsulation host.